Measuring and Explaining Charge Bargaining - Piehl, Anne Morrison (Journal of quantitative criminology, 2007)
Charge bargaining is a potentially important form of discretion in criminal sentencing that is obscured in many studies of sentencing outcomes. Our procedure to measure the difference in sentencing outcomes caused by plea bargain emphasizes the amount, in months, that the sentence length is reduced. Using this measure, we compare prosecutorial discretion across counties in two different states. We conclude that charge bargaining plays an empirically important role in determining sentencing outcomes. Furthermore, we find that measuring the distance (in months of prison time) moved during a charge bargain may provide a very different estimate of the discretion than is given by the rate of bargaining, which is the usual measure used. Although the rate of charge bargaining was higher in the voluntary guidelines state, its impact on sentences was greater in the presumptive guidelines jurisdiction, as predicted by Reitz ( 1998 ). We further observe a dramatic difference in predictions from shifting the case characteristics underlying the summary measure. This result reveals that distributional differences (either due to the underlying criminal activity or due to the overall level of severity of punishment) can easily obscure the inferences necessary for understanding the operation of the systems. Our finding of differential charge bargaining in these two jurisdictions should provide a caution when comparing the results of studies of disparity in sentencing across jurisdiction types.